2015
DOI: 10.1016/j.molonc.2015.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of anticancer aptamer AS1411 reveal a novel role for nucleolin in regulating Rac1 activation

Abstract: AS1411 is a G-rich quadruplex-forming oligodeoxynucleotide that binds specifically to nucleolin, a protein found on the surface and in the cytoplasm of most malignant cells but absent from the surface/cytoplasm of most normal cells. AS1411 has shown promising clinical activity and is being widely used as a tumor-targeting agent, but its mechanism of action is not fully understood. Previously, we showed that AS1411 is taken up in cancer cells by macropinocytosis (fluid phase endocytosis) and subsequently stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(116 citation statements)
references
References 51 publications
(83 reference statements)
7
109
0
Order By: Relevance
“…[26][27][28] The AS1411 aptamer specifically recognizes nucleolin, which is overexpressed in various cancer cells, including breast cancer, lymphocytic leukemia, hepatocellular carcinoma, prostate carcinoma and renal cell carcinoma. 25 We expected that the numerous aptamers in the elongated ssDNA would enhance the binding of the DNFs to target cells through multivalent interaction with the nucleolin. The EGR-1 and survivin genes are closely related to the development of breast cancer.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] The AS1411 aptamer specifically recognizes nucleolin, which is overexpressed in various cancer cells, including breast cancer, lymphocytic leukemia, hepatocellular carcinoma, prostate carcinoma and renal cell carcinoma. 25 We expected that the numerous aptamers in the elongated ssDNA would enhance the binding of the DNFs to target cells through multivalent interaction with the nucleolin. The EGR-1 and survivin genes are closely related to the development of breast cancer.…”
Section: Construction and Characterization Of The Dnfsmentioning
confidence: 99%
“…The AS1411 aptamer enables targeted delivery of the DNF to nucleolin-overexpressing cancer cells followed by internalization by receptor-mediated endocytosis. 24,25 The gene-silencing system can catalytically cleave two apoptosis-related mRNAs simultaneously, which would result in enhanced cancer therapy efficiency. Encouragingly, we found that the nanostructure collapsed in acidic conditions following the dissolution of the co-assembled magnesium pyrophosphate.…”
Section: Introductionmentioning
confidence: 99%
“…Methuosis was initially described in glioblastoma (GBM) cells ectopically expressing activated Ras or Rac1 (Overmeyer et al 2008). Subsequent studies have identified methuosis-like cell death phenotypes in other contexts, including lung adenocarcinomas with activating mutations in both K-Ras and EGFR (Unni et al 2015), prostate cancer cells exposed to an oligonucleotide aptamer, AS1411 (Reyes-Reyes et al 2015), thyroid carcinoma cells in which miR-199a-3p is ectopically expressed (Minna et al 2014), and GBM cells treated with small molecules (Overmeyer et al 2011; Kitambi et al 2014). To begin to explore the therapeutic potential of inducing methuosis in GBM and other cancers, we have developed a series of synthetic indole-based chalcones (indolyl- pyridinyl-propenones) that can elicit this form of cell death at low micromolar concentrations (Overmeyer et al 2011; Robinson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It results in in vitro cell growth inhibition in various human tumor cell lines including MCF-7 [61,62], HeLa, DU-145 and A549 [62], and in breast cancer tumor growth inhibition associated to reduced metastasis in in vivo MDA-MB-231 xenograft models [30]. More recently, the team of Bates has demonstrated that the antiproliferative activity of AS1411 correlated with its capacity to stimulate macro pinoicytosis through activation of Rac1 [63] causing methuosis [64], a new type of non-apoptotic cell death. Thus, AS1411 exhibits dual properties of targeting and killing tumor cells.…”
Section: As1411 Aptamer Conjugated Nps Targeting Nclmentioning
confidence: 99%